The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1074/jbc.m115.657668
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel Sequence Motif Recognized by the Ankyrin Repeat Domain of zDHHC17/13 S-Acyltransferases

Abstract: Background: S-Acylation, a protein lipidation process that is essential for neuronal functions, is catalyzed by zDHHC S-acyltransferases.Results: The ankyrin repeat (AR) domains of zDHHC17 and zDHHC13 recognize a novel unstructured peptide sequence in several unrelated proteins.Conclusion: Several proteins have independently acquired similar short peptide sequences for zDHHC17/13 binding.Significance: This is the first study to identify a motif recognized by AR-containing S-acyltransferases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
113
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(117 citation statements)
references
References 74 publications
3
113
1
Order By: Relevance
“…The consensus sequences for other lipidations such as myristoylation and isoprenylation were already identified as glycine in the Nterminal MGXXXS/T (M, Met; G, Gly; S, Ser; T, Thr; X, any amino acid) for myristoylation and cysteine in the C-terminal CAAX motif (C, Cys; A, an aliphatic amino acid; X, any amino acid) for isoprenylation [49]. Regarding the consensus sequence for palmitoylation, a very recent report identified a novel sequence motif that is recognized by the ankyrin repeat domain of DHHC17 and DHHC13, which is the first demonstration of a motif as consensus sequences of substrates recognized by ankyrin repeat-containing DHHCs [50]. A number of DHHC17 substrates and DHHC17-and DHHC13-interacting palmitoylated proteins, including SNAP-25b, SNAP-23, CSP, huntingtin, cytoplasmic linker protein 3 (CLIP3), and microtubule associated protein 6 (MAP6) contain a ΨβXXQP (Ψ, an aliphatic amino acid; β, a C-β branched amino acid Val, Ile, or Thr; X, any amino acid; Q, Gln; P, Pro) motif.…”
Section: Substrate Specificitymentioning
confidence: 99%
See 1 more Smart Citation
“…The consensus sequences for other lipidations such as myristoylation and isoprenylation were already identified as glycine in the Nterminal MGXXXS/T (M, Met; G, Gly; S, Ser; T, Thr; X, any amino acid) for myristoylation and cysteine in the C-terminal CAAX motif (C, Cys; A, an aliphatic amino acid; X, any amino acid) for isoprenylation [49]. Regarding the consensus sequence for palmitoylation, a very recent report identified a novel sequence motif that is recognized by the ankyrin repeat domain of DHHC17 and DHHC13, which is the first demonstration of a motif as consensus sequences of substrates recognized by ankyrin repeat-containing DHHCs [50]. A number of DHHC17 substrates and DHHC17-and DHHC13-interacting palmitoylated proteins, including SNAP-25b, SNAP-23, CSP, huntingtin, cytoplasmic linker protein 3 (CLIP3), and microtubule associated protein 6 (MAP6) contain a ΨβXXQP (Ψ, an aliphatic amino acid; β, a C-β branched amino acid Val, Ile, or Thr; X, any amino acid; Q, Gln; P, Pro) motif.…”
Section: Substrate Specificitymentioning
confidence: 99%
“…A number of DHHC17 substrates and DHHC17-and DHHC13-interacting palmitoylated proteins, including SNAP-25b, SNAP-23, CSP, huntingtin, cytoplasmic linker protein 3 (CLIP3), and microtubule associated protein 6 (MAP6) contain a ΨβXXQP (Ψ, an aliphatic amino acid; β, a C-β branched amino acid Val, Ile, or Thr; X, any amino acid; Q, Gln; P, Pro) motif. The consensus sequence was recognized by DHHC17 and DHHC13 via the ankyrin repeats domain in their cytosolic Nterminus [50]. The consensus sequences for the recognition by and catalytic activity of most DHHC proteins will need to be identified.…”
Section: Substrate Specificitymentioning
confidence: 99%
“…Usually two AR containing DHHC PATs are found in per genome, such as in mammals (Fukata et al, 2004), yeast (Roth et al, 2006), fly (Bannan et al, 2008), apicomplexan parasite (Frénal et al, 2013), nematode (Edmonds and Morgan, 2014), and plants (Yuan et al, 2013). It is thought that AR can help these PAT to recognize its specific targets for S-acylation (Lemonidis et al, 2015). However, other functions of AR that are independent from S-acylation were also found in some such PATs (Harada et al, 2003; Hemsley and Grierson, 2011; Yang and Cynader, 2011).…”
Section: Protein S-acyl Transferases (Pats)mentioning
confidence: 99%
“…A recent report highlights the important role of DHHC-ANK domains in the recognition of the substrate sequence. 36 The new substrate consensus sequence recognized by the DHHC17 and 13 ANK domains was detected in several proteins including, among others, SNAP25, SNAP23, and huntingtin. 36 Similarly, it was shown that the PDZ domain of DHHC5 binds glutamate receptor interacting protein (GRIP1b), facilitating the palmitoylation of GRIP1 band its subsequent trafficking to its dendritic localization.…”
Section: Zdhhc Proteins: Substrate-specificitymentioning
confidence: 99%
“…36 The new substrate consensus sequence recognized by the DHHC17 and 13 ANK domains was detected in several proteins including, among others, SNAP25, SNAP23, and huntingtin. 36 Similarly, it was shown that the PDZ domain of DHHC5 binds glutamate receptor interacting protein (GRIP1b), facilitating the palmitoylation of GRIP1 band its subsequent trafficking to its dendritic localization. 37 PDZ-mediated interactions between DHHC5 and neuronal PSD-95 protein was previously shown 38 and, in a separate study, a mutant of DHHC5 with a deletion of the PDZ domain (DHHC5 ÁPDZb) could not bind to PSD-95.…”
Section: Zdhhc Proteins: Substrate-specificitymentioning
confidence: 99%